2015
DOI: 10.1021/acsmacrolett.5b00755
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling Combined with Advanced Chemistry for the Rational Design of Efficient Graphene Dispersing Agents

Abstract: Pyrene-functional PMMAs were prepared via ATRP-controlled polymerization and click reaction, as efficient dispersing agents for the exfoliation of few-layered graphene sheets (GS) in easily processable low boiling point chloroform. In parallel, detailed atomistic simulations showed fine dispersion of the GS/polymer hybrids in good agreement with the experiment. Moreover, the molecular dynamics simulations revealed interesting conformations (bridges, loops, dangling ends, free chains) of GS/polymer hybrids and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Au 923 NCs are modeled as a set of Lennard-Jones (12-6 LJ) Au atoms according to Heinz et al 28 Graphene is modeled through the all-atom DREIDING force-field, 29 already employed for the study of carbon nanotube-and graphene-based polymer nanocomposites. [30][31][32] The interactions of Au and graphene atoms are modelled with a 12-6 LJ potential according to Lewis et al 17 All MD simulations are executed with the LAMMPS software 33 (see also S3, ESI †).…”
Section: Femtosecond Electron Diffractionmentioning
confidence: 99%
“…Au 923 NCs are modeled as a set of Lennard-Jones (12-6 LJ) Au atoms according to Heinz et al 28 Graphene is modeled through the all-atom DREIDING force-field, 29 already employed for the study of carbon nanotube-and graphene-based polymer nanocomposites. [30][31][32] The interactions of Au and graphene atoms are modelled with a 12-6 LJ potential according to Lewis et al 17 All MD simulations are executed with the LAMMPS software 33 (see also S3, ESI †).…”
Section: Femtosecond Electron Diffractionmentioning
confidence: 99%
“…Papadimitriou et al employed MD in conjunction with advance chemistry to study the conformations like bridges, loops, free chains, and dangling ends in GS‐pyrene functional PMMA nanocomposite. The main advantage of using the pyrene as modifier for functionalization purpose is their good compatibility with various polymer hosts that also renders graphene an adaptable nanofiller in nanocomposites.…”
Section: Atomistic Simulations To Characterize the Graphene‐polymer Nmentioning
confidence: 99%
“…Despite all these advantages, polymers are less dense and their structural strength is comparatively very low. In order to improve the strength of polymers, the properties of reinforcement/nanofiller play a decisive role . Polymers‐based nanocomposites exhibit high heat distortion temperature, curtailed scratch and mar resistance, noise damping, and tailored mechanical strength .…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [ 14 ] found that different processing routes to prepare graphene/polymer composites could have difference effects on the electrical conductivity of the composites due to the different dispersion level of graphene in the polymer matrix. In addition to experiments, extensive theoretical investigations, including molecular dynamics (MD) simulation [ 15 , 16 , 17 , 18 ], micromechanics modelling [ 19 , 20 ] and finite element method (FEM) [ 21 , 22 , 23 , 24 , 25 ], also observed the significant reinforcing effects of graphene and its derivatives. The mechanisms that underpin the prominent reinforcing effects can be attributed to graphene and its derivatives’ 2D structure features and their extremely high surface area, which result in excellent load transfer from the matrix to the reinforcements [ 1 , 8 , 11 , 20 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%